Efektivitas Penggunaan 3D Printing Berbasis Augmented Reality dalam Pembelajaran Biologi: Kajian Literatur Sistematis - KINANTHI ANGGRAINI; Lasinta Ari Nendra Wibawa (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2026)
This study is a systematic literature review examining the effectiveness of 3D printing integrated with Augmented Reality (AR) in Biology education. Thirteen peer-reviewed articles published between 2017 and 2025 were analyzed to evaluate three main aspects: learning effectiveness, 3D product development, and improvement in student learning outcomes or motivation. The findings indicate that 3D printing combined with AR consistently enhances conceptual understanding, technical skills, and student motivation, with reported effectiveness ranging from 49% to 90%. The learning products developed include cell models, DNA/RNA molecules, anatomical organs, flower models, and tactile tools for students with special needs, using software such as Blender, Tinkercad, and Ultimaker Cura, as well as PLA or recycled filaments. Improvements in learning outcomes were observed across cognitive, affective, and psychomotor domains, with average gains ranging from 20% to 83% across studies. This review confirms that integrating 3D printing with AR enriches learning experiences, promotes inclusive education, and enhances technological literacy in Biology. Future research is recommended to employ randomized experimental designs, standardize effectiveness metrics, and conduct long-term evaluations to assess knowledge retention and motivational impact more comprehensively.